Geotechnical Characterisation and Geoenvironmental Engineering IGC 2016 Volume 1 - Stalin, V. K.; Muttharam, M.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
The book comprises selected proceedings of the 2016 annual conference of the Indian Geotechnical Society. The technical papers presented on the theme "Geotechnical Characterisation and Geoenvironmental Engineering" highlight the modified geotechnical properties of soil admixed industrial waste and also the characteristics of soil with different pore fluid under varying test conditions. The major topics covered are (i) characterisation of soils, rocks and synthesised materials and (ii) geoenvironmental engineering and behaviour of unsaturated soil. This book will prove a valuable reference for researchers and practicing engineers alike.
THEME 1 : CHARACTERIZATION OF SOILS, ROCKS AND SYNTHESIZED MATERIALS -- Static Compaction Test and Determination of Equivalent Static Pressure -- Effect of Confining Pressure on Post Peak Behaviour of Igneous Rock -- Utility of Lime and Red Mud in Clay Soil Stabilization -- Geotechnical Characterization of Construction and Demolished (C&D) Waste -- Light Weight Deflectometer as a Compaction Quality Control Device -- A Study on Compressibility, Swelling and Permeability Behaviour of Bentonite- Sand Mixture -- Effect of Fines on Shear Strength of Sands -- Effect of Constant Energy Source on Coherence Function in Spectral Analysis of Surface Waves (SASW) Testing -- Comparison of Properties of Cohesive Soils Along East Coast of India -- Effect of Pore Size Distribution on Unconfined Compressive Strength -- Synthesis of Fly Ash-GGBS Blended Geopolymer Composites -- Local Strain Measurements in Triaxial Tests using On-Sample Transducers -- Geotechnical Characterization of Hill Slope Soils of Guwahati Region -- Effect of Box Size on Dilative Behaviour of Sand in Direct Shear Test -- THEME 4: GEOENVIRONMENTAL ENGINEERING AND BEHAVIOUR OF UNSATURATED SOILS -- Influence of Initial Conditions on Undrained Response of Soft Clays -- A Methedology to Determine Water Vapour Diffusion Characteristics of Geomaterials -- Atterberg Limits of Sand-Bentonite Mixes and the Influnce of Sand Composition -- Effect of Sample Thickness on Laboratory Determination of Gas Permeability of Buffer Material -- Biominerlisation as a Remediation Technique: a Critical Review -- Biopolymer Modified Soil: Prospects of a Promising Green Technology -- Factors Influencing Zeta Potential of Clayey Soils -- Experimental Analysis of Salt Diffusion in Compacted Clays by Through Diffusion and Half-Cell Technique -- A Study on Influence of pH and Organic Chemical on Adsorption Capacity of Red Earth -- Effect of Induced Osmotic Suction on Swell and Hydraulic Conductivity of an Expansive Soil -- Attenuation Characteristics of Laterite - Fly Ash - Bentonite Mix as Liner -- An Experimental Investigation on the Geoengineering Properties of Pond Ash-Bentonite Mixes -- Influence of Engineering Behaviour of Coal Ash on Design of Ash Dykes -- Virus Transport Through Heterogeneous Unsaturated Zone in Guwahati City in Assam Under Transient State Condition -- Behaviour Thresholds of Quarry-Dust Bentonite Mixes -- Index and Shear Strength Properties of Clay Soil Contaminated by Tannery Effluent -- Effect of pH on the Geotechnical Properties of Kaolinitic and Montmorillonitic Clay -- Influence of Geomembrane Stiffness on the Integrity of Landfill Covers: Centrifuge Modeling -- Studies on Desiccation Cracking Behaviour of Geofiber Reinforced Clay -- Shear Strength Parameters of Granite Rock-Mass: a Case Study -- Effects of Gypsum on Strength Behaviour of Lime Modified Pond Ash as an underground Stowing Material -- Stress-Dilatancy Relation of Sea Deposits Off Mumbai Coast -- Evaluation of Soil Parameters by using Light Cone Penetrometer.
Keywords: Engineering geology; Geotechnical engineering; Soil science; Geoengineering; Geotechnical Engineering and Applied Earth Sciences; Soil Science